Endoscopic features of drug-induced esophageal ulcer: “the kissing ulcer” - Silva, Felipe (2025)
Abstract Drug-induced esophageal ulcers constitute an acquired chemical injury to the esophageal mucosa, most frequently associated with tetracyclines, particularly doxycycline. We report a case of "kissing ulcers" diagnosed through esophagogastroduodenoscopy in a young woman undergoing doxycycline treatment for rosacea. The pathogenesis is linked to drug-specific factors, such as caustic effects, hyperosmolar properties, and prolonged mucosal contact with the medication, in addition to patient-specific risks, including esophageal motility disorders, reduced saliva production, and mid-esophageal anatomical compression. Clinically, patients commonly present with abrupt-onset chest pain, dysphagia, and odynophagia, while endoscopic findings often reveal mucosal erythema, erosions, and specular distribution esophageal ulcers (referred to as “kissing ulcers”). Management involves discontinuation of the causative drug, initiation of proton pump inhibitors or sucralfate, and implementation of preventive measures, such as ensuring adequate hydration during medication intake. This condition is generally self-limiting, with symptoms resolving within two weeks, underscoring the importance of prompt diagnosis and treatment to avoid potential complications.